Home energy cloud management system - Wang, Xiaochen (2014)
The exponential growth and availability of structured and unstructured data in terms of volume, variety and velocity necessitates the implementation of a platform for information processing and analysis. With the rapid growth of human population and fast urban development, energy demand has been continuously increasing. In particular, managing and minimizing energy consumption on a large facility based on its energy signatures is usually a difficult task for facility managers due to large data records and complexity. In this report, based on the existing Smart Energy Cloud System developed, Apache Cassandra, a novel database management system is set up to process and analyze data collected from a facility to achieve real-time and optimization of decentralized energy allocation. Energy consumption behaviors are obtained to acquire energy signatures of rooms using smart gate, which serves as a node. Single node and multi-node cluster will be set up to demonstrate the effectiveness of the capability of Apache Cassandra used for energy management.